2011
DOI: 10.2478/v10222-011-0023-7
|View full text |Cite
|
Sign up to set email alerts
|

Relations Between Occurrence of the Risk of Food-Drug Interactions and Patients’ Socio-Demographic Characteristics and Selected Nutrition Habits

Abstract: Key words: food-drug interactions, knowledge on drugs interactions with foodThe objective of the study was to investigate the patients' exposure to food-drug interactions, and to analyse the main factors leading to a risk of interactions in the examined patients. A high (62.4%) risk of food-drug interactions incidence, which may cause various complications in therapy, was found in the study. The majority of patients (52.8%) were not aware that the timing of drug intake in relation to meals may affect treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
48
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(51 citation statements)
references
References 15 publications
2
48
1
Order By: Relevance
“…In their study of food and drug interactions, Lopes et al asserted that 13% of the reported food and drug interactions were related to aspirin (acetyl salicylic acid (anti-inflammatory drug)), 10 cases (17%) to captopril (cardiovascular drug), and 18 cases (30%) to spironolactone, which had the highest number of interactions among the other studied drug categories. Their results on interactions of captopril are consistent with the present study findings [5]. In their study of food and drug interactions, Leibovitch et al reported interactions among cardiovascular, psychoactive, antibiotic, endocrine, gastrointestinal, and respiratory medications.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In their study of food and drug interactions, Lopes et al asserted that 13% of the reported food and drug interactions were related to aspirin (acetyl salicylic acid (anti-inflammatory drug)), 10 cases (17%) to captopril (cardiovascular drug), and 18 cases (30%) to spironolactone, which had the highest number of interactions among the other studied drug categories. Their results on interactions of captopril are consistent with the present study findings [5]. In their study of food and drug interactions, Leibovitch et al reported interactions among cardiovascular, psychoactive, antibiotic, endocrine, gastrointestinal, and respiratory medications.…”
Section: Discussionsupporting
confidence: 92%
“…Health care providers can prevent food and drug interactions and complications by careful drug selection and counseling for older patients [14]. The results of the study by Lopes on the evaluation of food and drug interactions were consistent with those of the present study and revealed that from the total food and drug interaction cases, 53% were related to cardiovascular drugs, 22% to antiinflammatory drugs, 18% to diuretic drugs, and 7% to gastrointestinal drugs [5]. Abbasi Nazari et al reported frequent incorrect use of hydrochlorothiazide, captopril, and gemfibrozil, and 44% of drug administration was incorrect in relation to meals in their study.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations